Dirty money coming home: Capital flows into and out of tax havens - Jakob Miethe; Lukas Menkhoff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We use recently released bilateral locational banking statistics of the BIS to show the full circle of international tax evasion via tax havens. White-washed money from tax havens is withdrawn from banks in non-havens if an information treaty is signed. This complements the stylized fact of such a reaction on outbound flows into tax havens. We find different time lags and other plausible structures in these reactions and a puzzling decline of the effect of treaties on capital flows over time.
Keywords: F38; G21; H26; 330